Authenticity without Essence: A Buddhist-Cognitive Critique of the ‘True Self’ in Spiritual Identity - Kempton H (Japan Bilingual Publishing Co., 2026)
ABSTRACT The concept of a ‘true self’ remains central to many contemporary spiritual narratives, often serving as a benchmark for authenticity and personal growth. However, this notion typically rests on essentialist assumptions that are increasingly challenged by both Buddhist philosophy and cognitive science. Drawing on the Buddhist doctrine of anattā (non-self) and empirical research on the constructed nature of identity, this article critiques the metaphysical idea of a stable, discoverable self. It argues that authenticity is better understood as a dynamic, relational, and ethically responsive process rather than a return to an inner essence. Through comparative analysis of Western philosophical models, postmodern critiques, and cognitive psychology, the paper demonstrates how identity is shaped by impermanence, interdependence, and contextual factors, and how essentialist assumptions persist despite substantial philosophic and scientific challenges. The article proposes a Buddhist-Cognitive (realist) model of authenticity grounded in impermanence, interdependence, and ethical engagement, extending the original critique by showing how descriptive findings from cognitive science can inform normative claims about spiritual practice and psychological well-being. This model reframes authenticity as a practice of ethical engagement and psychological coherence within a fluid and evolving self-system. By rejecting metaphysical permanence and embracing relational emergence, the article contributes to a pluralistic understanding of authenticity that is both philosophically rigorous and practically applicable in contemporary spiritual and psychological discourse.